Examining guidance and counseling students interpersonal communication skill based on semester level - Dewanti, Septinda Rima; Novitasari, Zeti (Psychology, Evaluation, and Technology in Educational Research, 2020)
Interpersonal communication has been widely studied and proven to be an important skill possessed by school counselor. Interpersonal communication skills are activities that transfer certain information appropriately by the context of the communication. The purpose of this study was to determine the differences in interpersonal communication skills of students majoring in guidance and counseling. The subjects of this study were students of the guidance and counseling department at Universitas Negeri Yogyakarta, who enrolled in the year 2017, 2018 and 2019. The research method used was quantitative research methods. Data analysis was performed using One-way Anova.The results of this study show that there is no difference in the interpersonal communication skills based on semester level.